PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Sandi Windia Primatama; Warsito Kawedar (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of good corporate governance (GCG) mechanisms and corporate social responsibility (CSR) on the company's financial performance with earnings management as a mediating variable. 138 samples selected of non-financial sector companies listed on Indonesia Stock Exchange from the period 2017-2019. The analytical method used in this study are multiple regression analysis and path analysis using SPSS software. The results showed that audit quality, institutional ownership, and independent commissioners each had a positive effect on the company's financial performance. Meanwhile, the board of directors, audit committee, corporate social responsibility, and earnings management have no effect on the company's financial performance. Furthermore, audit quality, institutional ownership, independent board of commissioners, board of directors, audit committee, and corporate social responsibility have no effect on earnings management. Path analysis result show that earnings management does not gives mediating effect on the relationship between the five proxies of good corporate governance mechanisms and corporate social responsibility with the company's financial performance.